2014
DOI: 10.1016/j.jesp.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Wanting other attitudes: Actual–desired attitude discrepancies predict feelings of ambivalence and ambivalence consequences

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription ACTUAL-DESIRED ATTITUDE DISCREPANCIES 2 AbstractFeelings of attitudinal ambivalence (subjective ambivalence) are important because they predict key consequences of attitudes (e.g., attitude-behavior correspondence, attitude stability).However, the field's understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 75 publications
4
75
0
2
Order By: Relevance
“…Also, most of the consequences of ambivalence discussed in this chapter have been obtained in the context of subjectively experienced ambivalence. Moreover, effects of objective ambivalence tend to be driven by subjective ambivalence (DeMarree, Wheeler, Brinol, & Petty, 2014). Although the existence of evaluatively incongruent associations (objective ambivalence) in our view is a prerequisite for experiencing subjective ambivalence, it is the more affective nature of the latter state that is the most consequential for what people think and do.…”
Section: A: Affectmentioning
confidence: 56%
See 2 more Smart Citations
“…Also, most of the consequences of ambivalence discussed in this chapter have been obtained in the context of subjectively experienced ambivalence. Moreover, effects of objective ambivalence tend to be driven by subjective ambivalence (DeMarree, Wheeler, Brinol, & Petty, 2014). Although the existence of evaluatively incongruent associations (objective ambivalence) in our view is a prerequisite for experiencing subjective ambivalence, it is the more affective nature of the latter state that is the most consequential for what people think and do.…”
Section: A: Affectmentioning
confidence: 56%
“…For example, ambivalence is known to lead to both elaboration and response amplification (i.e., the reduction of ambivalence; Hanze, 2001). Also, it has been shown that it is primarily subjective (and not objective) ambivalence, and the motivation to reduce it, that causes ambivalent attitude holders to have greater interest in attitude-relevant information (DeMarree et al, 2014). Along similar lines, egalitarian people who become aware of having prejudiced thoughts show increased attention to discrepancy-related information, supposedly with an aim to reduce this internal inconsistency (Devine, Monteith, Zuwerink, & Elliot, 1991;Monteith, 1993;Monteith et al, 1993).…”
Section: Systematic Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is based on the finding that discrepancies between a person's desires and the actual experience while taking the exam can create a sense of conflict, ambivalence, confusion, or lack of clarity. For example, discrepancies between people's actual and desired evaluations lead people to feel more ambivalent in that evaluation (DeMarree, Wheeler, Briñol, & Petty, 2014), and discrepancies between actual and desired levels of self-esteem undermine a person's self-clarity (DeMarree & Rios, 2014). This presumably occurs because, when a person's desired and actual evaluations are discrepant, their choices of behavioral responses to those two evaluations are likely to be in conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the consensus is that attitudes can affect actions, but a number of variables moderate the attitude-behavior relation (Ajzen & Fishbein, 1977; Cacioppo, Gardner, & Berntson, 1997; Crano, 2012; Fishbein & Ajzen, 1975; Petty & Krosnick, 1995). Of the variables identified as potential moderators of the attitude-behavior link, attitude ambivalence is one of the most promising, but has received perhaps the least attention (Conner & Armitage, 2008), though a resurgence of research on ambivalence has occurred over the last decade (e.g., DeMarree, Wheeler, Briñol, & Petty, 2014). …”
mentioning
confidence: 99%